Efficient removal of dyes from dyeing wastewater by powder activated charcoal/titanate nanotube nanocomposites: adsorption and photoregeneration - Lin, Yingchao; Ma, Jun; Liu, Wen; Li, Zeyu; Kai He (Environmental Science and Pollution Research, 2019)
Effective removal of dyes has been widely investigated by the adsorption of powder activated carbon and photodegradation by titanate nanotubes (TNTs). In this study, a facile one-step alkaline-hydrothermal method was applied to synthesize powder activated charcoal–supported TNTs (TNTs@PAC). Adsorption of three representative dyes, i.e., cationic methylene blue (MB), cationic rhodamine B (RhB), and anionic methyl orange (MO), onto TNTs@PAC was evaluated by the adsorption kinetic experiments and adsorption isotherms. The first 30 min is the main time phase of adsorption, and MB, RhB, and MO obtained the experimental equilibrium uptake of 173.30, 115.06, and 106.85 mg/g, respectively, indicating their final removal efficiencies of 100%, 69.36%, and 64.11%, respectively. The increase of pH value reduced adsorption capacity of MO (from 149.35 mg/g at pH of 2 to 96.99 mg/g at pH of 10), but facilitated MB adsorption, which was attributed to the charge distribution on the surface of TNTs@PAC and the charge of dyes at different pH. Furthermore, good capacity recoveries of MB by TNTs@PAC (>þinspace}99%) were observed after UV irradiation treatment, indicating the used TNTs@PAC can be easily recycled for the adsorption of MB by UV irradiation. Overall, TNTs@PAC is an effective process for remediation of dye-contaminated water because of its adsorption performance for all selected dyes and good regeneration capacity for MB.